Pengaruh Penggunan Media Puzzel Terhadap Kemampuan Daya Ingat Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di SMP Negeri Air Lesing Kabupaten Musi Rawas - Roibah, Roibah; Qomarullah, Muhammad; Amirudin, Muhammad Faizul (Edification Journal : Pendidikan Agama Islam, 2024)
The problem in this research is that the teaching and learning process is less effective, resulting in the failure to achieve the desired memory. The aim of this research is to determine the effect of puzzle media on the memory abilities of class VII students at SMP Negeri Air Lesing, Musi Rawas Regency. The research design took the form of a pre-test-post-test control group design. The results of this research show that classes that use puzzle media get higher learning outcomes than classes that do not use puzzle media. The average student learning outcomes during the post-test experimental class > control class (81.4 > 74.7). Based on the t-test analysis using the SPSS application in the final test with an error level of 5%, a significance value > 0.05 (0.001 > 0.05) was obtained, so Ho was rejected and Ha was accepted. Thus, it can be concluded that there is a significant influence of the use of puzzle media on the memory abilities of class VII students at SMP Negeri Air Lesing, Musi Rawas Regency. Puzzel Media, Memory